4CPS-265 Effect of dedicated pharmacist intervention in neurocritical care unit: before and after participating in multidisciplinary rounds. (March 2019) - Sa, E; Kim, AJ; Cho, Y; Cho, EJ; Lee, E; Sandy Jeong, R
Abstract : Background: Few studies have assessed the activities of a designated neurocritical care pharmacist (NCP) by reducing preventable adverse drug events and medication errors. Purpose: This study evaluated the effect on the pharmaceutical service by a dedicated NCP. Material and methods: A retrospective study was conducted to compare a pre-designated NCP period (from 1 May 2016 to 31 December 2016) and post-designated NCP (from 1 May 2017 to 31 December 2017). Intensive care unit (ICU) length of stay, ICU mortality, a total number of interventions, intervention rates per prescription and acceptance rate of NCP interventions were compared between the two groups. The types of interventions and relevant medications were investigated. Results: The total number of patients was 676 during the pre-NCP period and 769 during the post-NCP period. The presence of NCP pharmacists decreased ICU length of stay (B=−0.077 (−0.148–0.006), p=0.033), increased the clinically significant interventions (OR, 2.2 (1.5–3.1), p<0.001) and showed a tendency to reduce ICU mortality (OR, 0.7 (0.3–1.7), p=0.436). The number of interventions per prescription (0.5% vs. 0.3%, p=0.008), the intervention rate per 1000 patient-days (110.8 vs. 72.3, p<0.001) and incidences of clinically significant interventions (50.8 vs 22.5, p<0.001) were higher in the post-NCP group, respectively. In six medication types among the top 10 frequently intervened medications in the post-NCP period, no intervention was documented during the pre-NCP period were documented in six medication types. Conclusion: The presence of the designated NCP pharmacist had a positive impact on the patients' care in neurocritical care units. It was also associated with a significantly reduced ICU length of stay. References and/or acknowledgements: 1. Weant KA, et al. Cost effectiveness of a clinical pharmacist on a neurosurgical team. Neurosurgery2009:65:946–50; discussion 950–1. No conflict of interest.